MENENTUKAN SUPREMUM DAN INFIMUM HIMPUNAN DENGAN PYTHON - Purba, Dita Lovianna; Saragih, Dwita Lestari; Haloho, Eka Christy; Kaban, Rifka Elianti Br; Hutapea, Tri Andri (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2025)
ABSTRACT Real analysis is a branch of mathematics that deals with real numbers and related functions, where supremum (smallest upper bound) and infimum (largest lower bound) are fundamental concepts. Although essential in understanding limits, integrals, and series, these concepts are often considered abstract and difficult for students to understand. This research aims to simplify the understanding of the supremum and infimum concepts through a computational approach with the Python programming language. Using quantitative methods, algorithms are developed to determine the supremum and infimum of various types of sets, including discrete sets, intervals, and inequalities. The program utilizes the regex library for input parsing and the set() data structure to avoid duplication. Results show that the program is able to identify the supremum and infimum accurately, even for special cases such as the empty set or infinite limits. However, there are still limitations in handling complex mathematical expressions and inputs with infinite limits. This research shows that the integration of mathematical concepts with computational technology can be an innovative and applicable learning alternative in real analysis. ABSTRAK Analisis real merupakan cabang matematika yang membahas bilangan real dan fungsi terkait, di mana supremum (batas atas terkecil) dan infimum (batas bawah terbesar) menjadi konsep fundamental. Meskipun esensial dalam memahami limit, integral, dan deret, konsep ini kerap dianggap abstrak dan sulit dipahami mahasiswa. Penelitian ini bertujuan untuk menyederhanakan pemahaman konsep supremum dan infimum melalui pendekatan komputasi dengan bahasa pemrograman Python. Dengan metode kuantitatif, dikembangkan algoritma untuk menentukan supremum dan infimum dari berbagai jenis himpunan, termasuk himpunan diskrit, interval, dan ketidaksetaraan. Program memanfaatkan pustaka regex untuk parsing input dan struktur data set() untuk menghindari duplikasi. Hasil menunjukkan bahwa program mampu mengidentifikasi supremum dan infimum secara akurat, bahkan untuk kasus khusus seperti himpunan kosong atau batas tak hingga. Namun, masih terdapat keterbatasan dalam menangani ekspresi matematika kompleks dan input dengan batas tak hingga. Penelitian ini menunjukkan bahwa integrasi konsep matematika dengan teknologi komputasi dapat menjadi alternatif pembelajaran yang inovatif dan aplikatif dalam analisis real.